2008
DOI: 10.2169/internalmedicine.47.0547
|View full text |Cite
|
Sign up to set email alerts
|

Neuropathological Studies of Patients with Possible Non-Herpetic Acute Limbic Encephalitis and So-called Acute Juvenile Female Non-Herpetic Encephalitis

Abstract: Objective This study was to clarify the neuropathological findings of non-herpetic acute limbic encephalitis (NHALE) and so-called acute juvenile female non-herpetic encephalitis (AJFNHE

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 19 publications
0
4
0
1
Order By: Relevance
“…92 As described earlier, a study examining patients with autoimmune epilepsy (presenting with NORSE) found elevated levels of IL-6, TNF-α, IL-2, and IL-4 in the CSF, and elevated levels of IL-6 and TNF-α in the periphery. 29 Multiple small immunopathological biopsy and autopsy studies from patients with AIE [93][94][95][96][97][98][99][100] have demonstrated a variety of pathological changes. Across these studies, there is a predominance of perivascular lymphocyte infiltration with antibody or complement deposition.…”
Section: Generation Of Seizures In Aiementioning
confidence: 99%
“…92 As described earlier, a study examining patients with autoimmune epilepsy (presenting with NORSE) found elevated levels of IL-6, TNF-α, IL-2, and IL-4 in the CSF, and elevated levels of IL-6 and TNF-α in the periphery. 29 Multiple small immunopathological biopsy and autopsy studies from patients with AIE [93][94][95][96][97][98][99][100] have demonstrated a variety of pathological changes. Across these studies, there is a predominance of perivascular lymphocyte infiltration with antibody or complement deposition.…”
Section: Generation Of Seizures In Aiementioning
confidence: 99%
“…However, several problems still remain to be unresolved including the etiology of patients without anti-NMDAR antibody, the etiology of male patients, the lack of detectable ovarian teratomas in some patients, the reason why predominantly young adults are affected, the reason why many Japanese patients are reported (4,(8)(9)(10), and the reason why there is a good outcome in the long term without tumor removal.…”
Section: Differences In Clinical Features Between Female and Male Patmentioning
confidence: 99%
“…(Albayrak & Gorgulu, 2008;Barcikowska, 1979;Biemond, 1956;Chakraborty et al, 2014;Chessa et al, 2017;Couto et al, 2013;Dodgson, 1955;Freedman et al, 1984;Hiraga et al, 2014;Hwang et al, 2014;Ishida et al, 2006;Ishii et al, 2011;Jellinger et al, 2011;T. S. Kim et al, 1997;Kurokawa et al, 2005;Lapenta et al, 2015;Leroy et al, 2007;Matsuzono et al, 2013;Maximov et al, 2018;McKay & Cipolotti, 2007;McMurtray et al, 2014;Mizutani et al, 2020;Mumoli et al, 2014;Nixon et al, 2001;Nomoto et al, 2007;Obara et al, 2008;Obrador et al, 1957;Okamoto et al, 2008;Saito et al, 2007;Sapir et al, 2007;Seghier et al, 2014;Sener, 1998;Serrano-Castro et al, 2013;Shiihara et al, 2006;Shintaku et al, 2010;Shintani et al, 2000;Silva et al, 2018;Sperner et al, 1996;Turkalj et al, 2012;Yasui et al, 1999;Yoshimura et al, 1988)…”
Section: Late-infantile Metachromatic Leukodystrophyunclassified